Phagocytosis in the fruit fly, Drosophila melanogaster - Stuart, Lynda (Henry Stewart Talks, 2009)
Infectious diseases remain the commonest cause of premature mortality worldwide, The emergence of antibiotic resistant strains and the risks of bioterrorism have reinforced the importance of understanding the host-pathogen dynamic, It is hopeful that identifying the natural mechanisms used by the host to control infection will provide new avenues for therapeutic intervention, Model organisms such as Drosophila provide well-characterized, conserved and genetically tractable systems for exploring this dynamic, Drosophila are amenable to not only forward and reverse genetics but also hold great promise for small molecule screening and other unbiased approaches that will uncover evolutionarily conserved components of the innate immune system